Early Jesuit travellers in Central Asia, 1603-1721 - Wessels, C. (Cornelius) (Delhi : Book Faith India ; Kathmandu : Distributed by Pilgrims Book House, 1998)
With special reference to Tibet.
Previous ed.: The Hague : M. Nijhoff, 1924.
Keywords: Jesuits -- China -- Tibet Autonomous Region; Jesuits -- Asia, Central; Jesuits -- Biography; Tibet Autonomous Region (China) -- Description and travel; Asia, Central -- Description and travel